The Influence of TikTok Media on Student Decision Making in Online Shopping - Farah Faida; Juwita Putri Ananta (ORGANIZE: Journal of Economics, Management and Finance, 2025)
The rapid development of social media, especially TikTok, has changed the consumption landscape of the younger generation. This study aims to examine the extent to which the TikTok platform influences online purchasing decisions of college students. Through a survey involving 99 college students, this study analyzes the relationship between exposure to TikTok content and online purchasing behavior. Quantitative research methods were used with questionnaire instruments that measured the frequency of TikTok use, perceptions of TikTok's influence, and online purchasing behavior. Data were analyzed using correlation analysis to test the relationship between research variables. The results showed that TikTok has a significant influence in increasing brand awareness and consumer interest in certain products. However, its influence on overall purchasing decisions is still limited. Other factors such as price, product quality, and recommendations from friends and family remain the main considerations in the decision-making process. This study examines the role of TikTok as a trigger for online purchasing decisions of college students, considering the moderating role of demographic variables such as age and gender. The results of the analysis show that the influence of TikTok is stronger among female college students than male college students. In addition, college students with high frequency of social media use are generally more susceptible to TikTok's influence. These findings highlight the importance of market segmentation in designing effective marketing strategies on the TikTok platform.